The evolutionary landscape of colorectal tumorigenesis - Cross, W; Kovac, M; Mustonen, V; Temko, D; Davis, H; Baker, A; Biswas, S; Arnold, R; Chegwidden, L; Gatenbee, C; Anderson, A; Koelzer, V; et al. (Springer Nature, 2018)
The evolutionary events that cause colorectal adenomas (benign) to progress to carcinomas (malignant) remain largely undetermined. Using multi-region genome and exome sequencing of 24 benign and malignant colorectal tumours, we investigate the evolutionary fitness landscape occupied by these neoplasms. Unlike carcinomas, advanced adenomas frequently harbour sub-clonal driver mutations—considered to be functionally important in the carcinogenic process—that have not swept to fixation, and have relatively high genetic heterogeneity. Carcinomas are distinguished from adenomas by widespread aneusomies that are usually clonal and often accrue in a ‘punctuated’ fashion. We conclude that adenomas evolve across an undulating fitness landscape, whereas carcinomas occupy a sharper fitness peak, probably owing to stabilizing selection.